Effectiveness of psychoeducational interventions for the treatment of diabetes-specific emotional distress and glycaemic control in people with type 2 diabetes: A systematic review and meta-analysis. Issue 6 (December 2019) - Perrin, N.; Bodicoat, D.H.; Davies, M.J.; Robertson, N.; Snoek, F.J.; Khunti, K.
Highlights: The impact of 32 interventions on diabetes-specific distress was assessed using meta-analysis. Of these, 23 studies were analysed to assess their impact on glycaemic control. Overall significant reductions were seen for both distress and glycaemic control. Analyses to explore intervention characteristics that may mediate the effect were inconclusive. Further research is needed; specifically with distress as a primary outcome measure. Abstract: Aims: Psychological comorbidity, such as depression and/or diabetes-specific emotional distress (DSD), is highly prevalent in people with type 2 diabetes (T2DM) and associated with poorer treatment outcomes. While treatments for depression are well established, interventions specifically designed for DSD are sparse. The aim of this study was to determine interventions that successfully address DSD and HbA1c in people with T2DM. Methods: Seven databases were searched to identify potentially relevant studies. Eligible studies were selected and appraised independently by two reviewers. Multiple meta-analyses and meta-regression analyses were performed to synthesise the data; the primary analyses determined the effect of interventions on DSD, with secondary analyses assessing the effect on HbA1c. Results: Thirty-two studies (n = 5206) provided sufficient DSD data, of which 23 (n = 3818) reported data for HbA1c. Meta-analyses demonstrated that interventions significantly reduced DSD (p = 0.034) and HbA1c (p = 0.006) compared to controls, although subgroup meta-analyses and meta-regression to explore specific intervention characteristics that might mediate this effect yielded non-significant findings. Conclusions: The findings demonstrate that existing interventions successfully reduce DSD and HbA1c in people with T2DM. While promising, deductions should be interpreted tentatively, highlighting a stark need for further focused exploration of how best to treat psychological comorbidity in people with T2DM.